Keterlibatan Guru PAK SMU Negeri Se-Kota Kupang dalam Pelayanan Gereja - Daud Saleh Luji; Indriani Lopo; Ana V. Soinbala (Sekolah Tinggi Teologi Kalimantan, 2021)
The purpose of writing this article is to determine the involvement and activeness of Christian Religious Education Teachers at Public Middle Schools in Kupang City in the ministry of clerical affairs as presbyters and as categorical servants, especially in the category of children and adolescents or what is often called Sunday school. The method used in this study is a qualitative method by interviewing 41 Christian Religious Education Teachers spread across 12 State Public Middle Schools in the city of Kupang, East Nusa Tenggara. From the results of the study, it was found that although this Christian Religious Education teacher had a correct understanding of the background of his attendance at school, namely Christian Religious Education teachers were church servants sent to serve congregations in schools, but most Christian Religious Education teachers did not have a relationship with the church. or not yet involved in the church ministry where he is a member, either as a presbyter or as a minister of children and youth (Sunday school). This conclusion was stated based on the informant's admission during the interview that 1) They did not have free time to be involved in church services, 2) Church services had many people taking care of it so they did not need to be involved, 3) Christian religious education teachers were paid by the state, not church so that they focus more on taking care of teaching in schools than in church.Tujuan dari penulisan artikel ini adalah untuk mengetahui keterlibatan dan keaktifan Guru-guru PAK yang ada di Sekolah Menengah Umum (SMU) Negeri se-Kota Kupang dalam pelayanan bidang kemajelisan gereja sebagai presbiter dan sebagai pelayan kategorial khususnya kategorial anak dan remaja atau yang sering disebut sekolah minggu. Metode yang dipakai dalam penelitian ini adalah metode kualitatif dengan mewawancarai 41 Guru PAK yang tersebar di 12 SMU Negeri yang ada di wilayah Kota Kupang, Nusa Tenggara Timur. Dari hasil penelitian ditemukan bahwa walaupun Guru PAK ini memiliki pemahaman yang benar tentang latarbelakang kehadirannya di sekolah yaitu guru PAK adalah pelayan gereja yang diutus untuk melayani jemaat di sekolah-sekolah, namun sebagian besar guru PAK belum memiliki hubungan dengan gereja atau belum terlibat dalam pelayanan gereja, dimana ia sebagai anggotanya, baik sebagai presbiter maupun sebagai pelayan anak dan remaja (sekolah minggu). Kesimpulan tersebut dikemukakan berdasarkan pengakuan informan pada saat wawancara bahwa 1) Mereka tidak punya waktu luang untuk terlibat dalam pelayanan di gereja, 2) Pelayanan gereja sudah banyak orang yang mengurusnya karena itu mereka tidak perlu terlibat, 3) Guru PAK digaji oleh negara bukan gereja sehingga mereka lebih fokus mengurus pengajaran di sekolah dari pada di gereja.